Forças impulsoras e restritivas para o trabalho em equipe de enfermagem em unidade de urgência e emergência - SILVA, Ana Paula (2009)
Teamwork is considered an essential tool in the process of improving health care, particularly emphasized in the Unique Health System guidelines as one of the axes that make it feasible the implementation of national health policy. It is a great challenge to both practitioners and managers, given its complexity. This is a descriptive exploratory study aimed at analyzing propelling and restrictive forces for nursing teamwork in an Adult Emergency and Urgency Unit of a public hospital through Kurt Lewin s approach. Mapping such forces enables managers to better deal with daily challenges, since they make it possible to categorize them into three related aspects: the SELF dimension- which includes personal factors, the OTHERincluding factors concerning interpersonal and ENVIRONMENTAL relations- which are part of elements not belonging to individuals, but to the environment. This is an investigation carried out in a school hospital located in the Midwestern Brazil, with 44 professionals taking part constituting the nursing team. Data was collected through questionnaire, submitted to content analysis process, categorized into dimensions previously defined. The outcomes showed balance in the teamwork forces domain, except concerning the ENVIRONMENTAL dimension, which result points to strong trends towards restrictive forces. The balance identified in the other dimensions signals that teamwork stagnation exists in the study group, which shows the need for interventions in order to stimulate and potentialize propelling forces and try to immobilize and transform restrictive forces. In the SELF dimension individual attributes, good relationship, friendship/love are seen as propelling forces, whereas individual limitations, absenteeism, health compromised, and technical competence limited are seen as restrictive ones. In the OTHER dimension, teamwork potential and force, active management posture and commitment/competence of both team and supportive areas are seen as propelling forces. As propelling forces in the same proportion relational limitation for teamwork and management posture which harm their work, as well as the harmed interpersonal relationship. Regarding the ENVIRONMENT, the propelling aspects are: proper setting and physical structure, efficient nursing records and integration between the clinical and supportive areas. Among restrictive aspects, dynamics and inadequate functioning of the unit, limited physical structure, shortage of material/equipment, and limited pharmacy service are highlighted. Identification of such factors shows that in the EUU there is a force field which needs to be developed towards teamwork, which may result in the betterment of quality of assistance and working conditions. For this reason, they need to be part of the institutional planning. Mapping such forces has enabled a concrete and objective view of the limitations and potential of the team studied, showing ways to orient changing processes. As a tool to be incorporated in the human resources management models for healthcare, this referential helps developing strategies to mobilize individual synergy and working teams, as well as with the elements favoring its effectiveness.